Peran Penting Pengolahan Data Dalam Transformasi Bisnis Melalui Analisis - Sofiya Azzara Rafles; Muhammad Irwan Padli Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In this latest business era, data processing is very important for companies. The reason is, the results of the data processing process are needed to produce business decisions. Data processing is a process that replaces raw data as useful and practical information received. Raw data is generally in the form of numbers or records that are still random and uncompiled, as a result it requires a processing process to convert it as a useful issue using certain techniques and methods. A data scientist or a team of data scientists typically handles data processing, which needs to be done correctly to avoid having an adverse effect on the finished product or data output. Data is first processed in its unprocessed state before being transformed into a more readable format (graphs, documents, etc.) that allows employees across the organization to process and use the data on computers.